Inovasi Pembelajaran Fisika Melalui Mobile learning Adaptif: Tinjauan Pustaka - Simarona, Nuri (Universitas Tanjungpura, 2024)
This study aims to examine innovations in physics education through the application of adaptive mobile learning. This literature review analyzes various studies and research conducted regarding the utilization of mobile technology in adaptive physics learning at the high school level. The scope of the research includes the effectiveness of adaptive mobile learning in enhancing conceptual understanding of physics, fostering learner independence, as well as promoting student interactivity and engagement. The research method employed is a systematic literature review, collecting and analyzing relevant research articles from national (Sinta) and international (Scopus) journal databases published in the last five years. The analysis instrument used includes thematic analysis to identify key themes and gaps in existing research. The results indicate that adaptive mobile learning has great potential in facilitating more personalized and interactive learning experiences. It has been shown to be effective in improving students' conceptual understanding of physics and their learning autonomy. However, several previous studies have indicated certain technical challenges and limitations that need to be addressed to optimize its implementation. The conclusion of this research is that innovations in physics education through adaptive mobile learning significantly contribute to students' learning experiences. Suggestions and recommendations for future research include further development and application of adaptive mobile learning, as well as more in-depth evaluations of its effectiveness across various physics learning contexts.